Antitheatricality and the Body Public. - Freeman, Lisa A. (Haney Foundation, 2016)
In an exploration of antitheatrical incidents from the seventeenth to the twentieth centuries, Lisa A. Freeman demonstrates that at the heart of antitheatrical disputes lies a struggle over the character of the body politic that governs a nation and the bodies public that could be said to represent that nation.